2014
DOI: 10.1105/tpc.114.132738
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome-Mediated Degradation of FRIGIDA Modulates Flowering Time in Arabidopsis during Vernalization

Abstract: Winter-annual accessions of Arabidopsis thaliana require either exposure to cold stress or vernalization to initiate flowering via FRIGIDA (FRI). FRI acts as a scaffold protein to recruit several chromatin modifiers that epigenetically modify flowering genes. Here, we report that proteasome-mediated FRI degradation regulates flowering during vernalization in Arabidopsis. Our genetic and biochemical experiments demonstrate that FRI directly interacts with the BTB (Bric-a-Brac/Tramtrack/Broad Complex) proteins L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 49 publications
5
59
0
Order By: Relevance
“…There are several regulatory pathways that converge to regulate FLC: the FRIGIDA pathway activates FLC expression, the autonomous pathway down regulates FLC , and vernalization epigenetically silences FLC in response to prolonged cold. All of these pathways involve a set of antisense transcripts, collectively named as COOLAIR (Swiezewski et al ; Hornyik et al ; Liu et al ) and COLDAIR (Heo and Sung ; Hu et al ). Epigenetic regulation of FLC by proteins and long noncoding RNAs in transcription levels have been extensively studied (Bastow et al ; Sung and Amasino ; Margueron et al ; Sung et al ; Schmitz and Amasino ; Choi et al ; Heo and Sung ; Jeon and Kim ; Kim and Sung ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several regulatory pathways that converge to regulate FLC: the FRIGIDA pathway activates FLC expression, the autonomous pathway down regulates FLC , and vernalization epigenetically silences FLC in response to prolonged cold. All of these pathways involve a set of antisense transcripts, collectively named as COOLAIR (Swiezewski et al ; Hornyik et al ; Liu et al ) and COLDAIR (Heo and Sung ; Hu et al ). Epigenetic regulation of FLC by proteins and long noncoding RNAs in transcription levels have been extensively studied (Bastow et al ; Sung and Amasino ; Margueron et al ; Sung et al ; Schmitz and Amasino ; Choi et al ; Heo and Sung ; Jeon and Kim ; Kim and Sung ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in plants have demonstrated that the ubiquitin/proteasome pathway is an essential component of the regulatory networks controlling many important cellular processes, including growth and development (Figueroa et al, 2005;Hu et al, 2014), as well as defense responses (Zeng et al, 2004). Among the three major enzymes in this pathway, the E3 ubiquitin ligases are responsible for controlling the specificity of target protein recognition and degradation via the 26S proteasome.…”
Section: Introductionmentioning
confidence: 99%
“…It is not known whether COLDAIR may have roles in the autonomous pathway so far. Interestingly, recently data showed that COLDAIR is involved in FRIGIDA pathway [73], and a putative histone methyltransferase SDG7, which is essential for cold induction of VIN3, can elevate the expression levels of COLDAIR, as well as COOLAIR [74]. Considering the partial temporal overlap of expression patterns during vernalization between two lncRNAs [51], it would be interesting to investigate the possible connection between the sense COLDAIR and antisense COOLAIR induction, and how they integrate to coordinate FLC silencing during vernalization.…”
Section: Lncrna Coldair and Flc Regulationmentioning
confidence: 97%